PELAKSANAAN PENDIRIAN BADAN USAHA MILIK DESA (BUMDESA) DALAM MENINGKATKAN PEREKOMIAN MASYARAKAT DI DESA TANJUNG KECAMATAN KOTO KAMPAR HULU KABUPATEN KAMPAR - Siti Ulva; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Implementation of Establishment of Village Owned Enterprises in improving community economy in sub-district of Kampar Kara Kampar upstream Kampar district is an effort to see whether the development of bumdesa implemented in accordance with the purpose of the establishment of the bumdesa. Establishment of a Village Owned Enterprise Tanjung is intended to establish business entities engaged in areas compatible with village authorities, able to provide services to the community, mobilize the village economy and contribute to village income. Until now, BUMDesa shoot hope is difficult to develop because the existing funds are not well managed due to lack of human resources management, members of BUMDesa do not know how to manage funds properly and lack of computer control due to lack of coaching to members.The theory used based on Village Regulation number 02 of 2016 on the Implementation of Establishment of BUMDesa. The research method used is descriptive qualitative. Informants in this study are village officials and administrators BUMDesa Tunas Harapan and community totaling as many as 6 people. Sampling technique using purposive sampling with certain consideration. The result of research that the implementation of the establishment of the Village Owned Enterprises in improving the economy of the people in the village of Tanjung Kampar Kampar hill sub-district is not fully implemented because in the implementation there are still shortcomings This is caused by several factors such as the management of unfavorable business units, village and the lack of cooperation with other institutions. Factors that influence the community participation is still lacking, because the community has not felt the benefits of BUMDesa, human resources (HR) that still lack the ability and expertise in managing BUMDesa in accordance with its function and lack of coordination between the Village side with the management of BUMDesa. In addition, it is necessary to procure training and development of human resources (HR) BUMDesa management to increase the ability, skill and adequate insight in running the planned business.Keywords : Implementation, BUMDesa, Community Economy